Renin activity in human hypertension - Thomas, G (1976)
This thesis is concerned with the renin-angiotensin system in essential hypertension. Humoral agents have been sought in the causation of high blood pressure for many years. The role of the renin- angiotensin system in hypertension remained controversial, but, gradually, the components and functions of this complex hormonal system were elucidated. Derangements of the system were confirmed in various examples of secondary hypertension, but the role of the renin-angiotensin system in essential hypertension remains unclear. The belief that essential hypertension represents an homogeneous group of patients has been questioned in recent years, and this has led to the attempt to separate essential hypertensive patients into renin subgroups. One of the most intensively investigated has been that with low-renin, but whether or not this group represents a distinct entity is uncertain. An important hypothesis attributes this 'syndrome 1 to an excess of an unknown mineralocorticoid. This work was undertaken to reappraise the role of renin in essential hypertension. Two major questions were considered: Is the activity of the renin-angiotensin system similar in essential hypertension and in the general population? Does low-renin hypertension exist as a separate entity attributable to mineralocorticoid excess? In answering these questions many variables other than renin, including age, sex, blood pressure, sodium, potassium, plasma volume and aldosterone, and their interrelationships were considered. Plasma renin activity is an index of the activity of the renin-angiotensin system, and the method used in its measurement has been described in considerable detail. Volunteers to have their arterial pressure measured were sought amongst the employees of A.E.R.E. Harwell and two general practices in Wantage and Didcot. From them two samples of people willing to co-operate were chosen: 89 with arterial pressures above 100 mm Hg and 89 of similar age and sex with diastolics below 90 mm Hg. All subjects with high blood pressure who had received treatment or who had symptoms from it were excluded. Investigations showed that subjects with high pressures conformed to the diagnosis of essential hypertension. RENIN IN ESSENTIAL HYPERTENSION Blood was withdrawn for the measurement of plasma renin activity after the subject had been lying down for 2 hours (supine) r after being up and around for 2 hours (erect), and 1 hour after an intravenous injection of frusemide (1 mg/kg). The renin responsiveness or change in plasma renin activity after stimulation was expressed in absolute and in percentage terms. In essential hypertension plasma renin and its responsiveness were found to be suppressed compared to control subjects. Reasons for the reduction in plasma renin and in renin responsiveness in essential hypertension are uncertain, but various factors are known to affect renin and were considered Plasma, urinary and total body potassium, plasma, urinary and total exchangeable sodium, and plasma volume were studied but did not account for the difference. Age was shown to correlate inversely with renin and its responsiveness in patients with hypertension and in controls, but the groups were age matched. The effects of previous antihypertensive drugs on renin levels were excluded by rejecting previously treated patients. Females tended to have lower plasma renin activity and responsiveness than males, but those with hypertension were sex matched with the controls. However, blood pressure was shown to be inversely related to plasma renin and its responsiveness in both groups. Thus, reduced plasma renin activity and responsiveness appears to be a general feature of essential hypertension. The suppression of renin is probably a result of the combined effect of many factors on renin release, but blood pressure itself has been shown to be an important contributor. LOW-RENIN HYPERTENSION An analysis of the distributions of plasma renin and renin responsiveness showed the logarithms of the renin variables to be normally distributed with no evidence of bimodality. This suggests that the low-renin state forms part of a continuum in hypertension rather than a distinct diagnostic entity. An attempt was made to separate the subjects with high arterial pressure into renin subgroups in a statistically acceptable way, while utilizing basal, stimulated and renin responsiveness data. The distributions of plasma renin and renin responsiveness were divided into three equal subgroups (lower, mid and upper) on the understanding that if a low- renin subgroup existed it would be contained in the lower third of the distributions. Plasma renin correlated significantly with responsiveness; in view of our method of defining low-renin hypertension, the decreased responsiveness in the low-renin subgroup could not be used to support its existence as a separate entity. This strengthens the argument against the use of stimuli to define a low-renin subgroup in essential hypertension. The hypothesis that an unknown mineralocorticoid is involved in the aetiology of low-renin hypertension did not withstand critical examination. Total exchangeable sodium, plasma volume, total body potassium and 24 hour urinary potassium excretion were measured in the three renin sub- groups of essential hypertension; the characteristic findings of an excess of an aldosterone-like mineralocorticoid were absent. It is proposed that low-renin hypertension represents no more than the lower end of the normal distribution of renin in essential hypertension. However, many factors including age and blood pressure may modify the renin status and need to be taken into account in the interpretation of individual values.